PELATIHAN PEMASARAN BERBASIS ONLINE DAN PENDAMPINGAN MANAJEMEN USAHA BAGI KELOMPOK WANITA TANI SEKARARUM DESA SEKARSARI - Ming Ming Lukiarti; A. Aviv Mahmudi; Dian Ayu Liana Dewi (Universitas YPPI Rembang, 2021)
Sekarsari Village is one of the villages located in Sumber District, Rembang Regency. Sekarsari Village has 5 hamlets, Sekararum, Klampok, Semendangsapi, Deresan, and Kaligenting. The ares of Sekarsari Village is approximately 10,000 hectares with a population of 3,500 people. There is alot of potential in Sekarsari Village, namely, plants of chilies, tomatoes, shallots, empon-empon, bamboo crafts and rabbits livestock. Based on the result of field observations that have been carried out, there are several problems faced by Kelompok Wanita Tani Sekararum Desa Sekarsari Kecamatan Sumber, namely: lackof product promotion so that marketing is hampered, lack of knowledge of appropriate marketing strategies, lack of pages or social media specifically to promote products, lack of skills in presenting product photos that are able to attract consumer tastes, there is no business financial accounting. The objectives of this program are: increasing knowledge and skills in implementing online produst marketing strategies, increasing kowledge and managing social media accounts for promotion, increasing knowledge and skills in using mobile phones as a promotional support tool, conducting training and mentoring to improve the management system to make it more planned and measureable. The output of this program is: increased turnover, having social media accounts, publications of scientific journals, and mass media publications, the method of implementations is by holding online and offline marketing training as well as direct business management assistance to members of the Kelompok Wanita Tani Sekar Arum.Keywords : Online Marketing, Sekarsari, Sekararum, Farmer Woman